About the nature of the crime of collusion of article 384 of the Criminal Code: Analysis of the jurisprudential debate - Chanjan Documet, Rafael (2022)
This article analyzes the nature of the crime of collusion regulated in article 384 of the Peruvian Penal Code, based on the recent jurisprudence of the Supreme Court of Justice. The relationship between the illicit of the first paragraph of the aforementioned article -called “simple collusion”- and the second paragraph -called “aggravated collusion”, its protected objects and its nature of crimes of injury or danger will be examined. On this point, a critical analysis of some jurisprudential pronouncements will be made and a position will be adopted on the autonomous nature of both crimes in order to solve practical problems such as the moment of consummation of the crime, the attempt and criminal participation.